Membangun Brand Image dengan menggunakan Sosial Media di Kedai Kopi 56 - Vera Novilia; Elfan Wahyu Mulyana (Cv. Utility Project Solution, 2022)
This activity aims to build a good brand image by using social media. This method can help these MSMEs to further develop in their business to be recognized by the community in Batam City. The object used in this activity is one of the MSMEs in Mitra Raya Market called Kedai Kopi 56. The problem with this coffee shop is the lack of promotion on social media and so far they have used word of mouth and no social media. Therefore, the solution is using Instagram social media to make it easier to provide information and implement advertisements. The method used in this activity is interviews and documentation at the Kedai Kopi 56. The results obtained after implementing social media are that coffee shops are more crowded than before, with a lot of shared posts on Instagram accounts to their friends and saving posts as references for places to eat.